THE URGENCY OF NATIONAL SECURITY COUNCIL (NSC) IN THE CONTEXT OF CYBER SECURITY AS A SUB SYSTEM OF NATIONAL SECURITY TO PROTECT STATE AND PEOPLE - Sumantri Sumantri (Journal of Social Political Sciences, 2020)
The 21st  century,  the era of globalization characterized by free fight competition,  advanced  information  and communication  technology, and  a borderless world has  in one side  make possibly  the entrance of  any  values  of ideology, politic, economy, socio culture, defense and security that can either   be threats or challenges for  any countries, in the other side democracy and human rights promoted by  globalization awakening the universal awareness of  human safety from any threat such as war, ethnic cleansing, communal conflict, and other physical and non physical threats. Despite the universal awareness of human safety, insecurity condition  and internal political problem  of any country will certainly affect the national security.